Lithium iron phosphate material capable of reducing charging polarization and preparation method and application thereof

By regulating the particle size and doping Ti elements in the lithium iron phosphate positive electrode material, the polarization problem during constant power charging is solved, the energy density and discharge capacity of the battery are improved, and more efficient charging and discharge performance is achieved.

CN119447285AInactive Publication Date: 2025-02-14XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411532303.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The lithium iron phosphate positive electrode material has polarization during constant power charging, which leads to the inability to fully charge the battery and the discharge capacity is low, affecting the performance of the battery capacity.

Method used

Through the dual methods of particle size regulation and metal doping, the micromacrostructure of lithium iron phosphate materials is optimized. Specific measures include reducing the particle size of lithium iron phosphate particles to 0.7-0.9 μm, and doping 2000-6000 ppm of Ti elements into the material to form a titanium framework, and improving the conductivity and charge and discharge performance of the material.

Benefits of technology

It effectively reduces charging polarization, improves the energy density and discharge capacity of the battery, ensures that the battery can be fully charged, extends the charging time, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447285A_ABST
    Figure CN119447285A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy batteries, and particularly relates to a lithium iron phosphate material capable of reducing charging polarization and a preparation method and application thereof. The lithium iron phosphate material is sphere-like lithium iron phosphate particles doped with a Ti element, the doping amount of the Ti element is 2000-6000 ppm, and the D50 of the sphere-like lithium iron phosphate particles is 0.7-0.9 [mu] m. Starting from the structure and composition of the material, the micro-macro structure of the lithium iron phosphate material is optimized and adjusted through dual combination of particle size regulation and metal doping, the compaction density of the material is ensured while the dynamic performance of the material is improved, the polarization degree of the material in the constant-power charging process is reduced, and the gram capacity of the material is improved; and the energy density of the battery is improved. The problem that during constant-power charging, the polarization of the charging tail end is large, and the battery cannot be fully charged, so that the discharging capacity is low is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy batteries, and in particular relates to a lithium iron phosphate material capable of reducing charging polarization, and a preparation method and application thereof. Background Art

[0002] Due to the non-renewable nature of fossil energy and the pollution it causes during use, the world has turned its attention to more low-carbon and environmentally friendly forms of energy utilization. At the same time, energy storage media represented by lithium-ion batteries have become an important part of the new energy field due to their significant advantages such as high energy density, pollution-free, and long life. As one of the representatives of lithium-ion batteries, lithium iron phosphate batteries are widely used in new energy vehicles and energy storage fields due to their stable structure, high safety performance, and long cycle life.

[0003] In lithium-ion batteries, from the perspective of materials, the theoretical mass specific capacity of lithium iron phosphate cathode material is 170mAh / g. After being made into a finished battery cell, the mass specific capacity is about 140mAh / g. Its gram capacity is lower than that of lithium cobalt oxide and ternary materials (about 270mAh / g). At the same time, the material compaction density is low (2.3g / cm 3 About), while the theoretical specific capacity of graphite, a commonly used negative electrode material, is 372mAh / g, and when the battery is prepared, in order to prevent the precipitation of dendrites, the negative electrode capacity in the lithium-ion battery is usually in excess, and the actual capacity is determined by the positive electrode capacity. Therefore, with the continuous development of lithium-ion batteries, positive electrode materials have become one of the important bottlenecks restricting the development of lithium-ion batteries, and modification from the material synthesis end has become an effective means to improve the performance of lithium iron phosphate positive electrode materials. At the same time, since the entire lithium-ion battery system still uses liquid electrolyte, the lithium ion migration coefficient is less than 1, which inevitably produces a concentration difference during charging, resulting in concentration polarization and electrochemical polarization during the charging process. This polarization phenomenon is particularly significant at the end of charging (under high SOC state), and due to the existence of polarization, the instantaneous voltage is higher than the equilibrium voltage, thereby reaching the charging cut-off voltage prematurely and triggering the charging process to stop, causing the battery to be unable to reach a full charge state, thereby affecting the battery capacity. Therefore, more lithium iron phosphate materials need to be invested in the design of the battery cell to achieve the design capacity of the battery, which increases the manufacturing cost of the battery and reduces the competitiveness of the product.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] In view of the shortcomings and defects of the prior art, the present invention aims to provide a lithium iron phosphate material and its preparation method and application that can reduce charging polarization. Starting from the structure and composition of the material, the present invention optimizes and adjusts the micro- and macroscopic structures of the lithium iron phosphate material through the dual combination of particle size regulation and metal doping, improves the dynamic performance of the material while ensuring the compaction density of the material, and reduces the polarization degree of the material during constant power charging, thereby increasing the gram capacity of the material and improving the energy density of the battery. It solves the problem that during constant power charging, the polarization at the end of charging is large, and the battery cannot be fully charged, resulting in a low discharge capacity.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a lithium iron phosphate material, wherein the lithium iron phosphate material is spherical lithium iron phosphate particles doped with Ti element, the doping amount of the Ti element is 2000-6000 ppm, and the D50 of the spherical lithium iron phosphate particles is 0.7-0.9 μm.

[0008] Furthermore, the compaction density of the lithium iron phosphate material is not less than 2.45 g / cm 3 , the gram capacity is not less than 143mAh / g.

[0009] In a second aspect, the present invention provides a method for preparing a lithium iron phosphate material. First, a lithium source, an iron source, a phosphorus source and a titanium source are dispersed by ball milling to make the powders uniformly mixed, and then high-temperature calcination, natural cooling and then crushing by air flow milling to obtain a lithium iron phosphate material with spherical particles with a D50 of 0.7 to 0.9 μm, wherein the doping amount of the Ti element in the lithium iron phosphate material is 2000 to 6000 ppm.

[0010] Furthermore, the titanium source is titanium dioxide.

[0011] Furthermore, the D50 of the titanium dioxide is 200-300 nm.

[0012] Furthermore, the temperature of the high temperature calcination is 650°C-850°C.

[0013] Furthermore, the high temperature calcination time is 8 to 10 hours.

[0014] In a third aspect, the present invention provides an application of a lithium iron phosphate material, the application comprising using the lithium iron phosphate material described in the first aspect or the lithium iron phosphate material prepared by the preparation method described in the second aspect as a positive electrode material of a lithium-ion battery to reduce charging polarization.

[0015] Furthermore, the negative electrode active material of the lithium-ion battery is graphite.

[0016] Furthermore, the energy density of the lithium-ion battery is not less than 172Wh / kg.

[0017] Compared with the prior art, it has the following beneficial effects:

[0018] The lithium iron phosphate material of the present invention can ensure both the charging capacity and the compaction density of the material, thereby ultimately improving the energy density of the battery and avoiding the problem of low discharge capacity.

[0019] In the process of material preparation, the present invention adopts a solid phase sintering method to synthesize and modify the material in view of the polarization phenomenon existing in the lithium iron phosphate battery during the charging process, especially the situation that the polarization phenomenon further increases with the increase of the SOC degree, resulting in the battery being unable to be fully charged and affecting the capacity of the lithium iron phosphate material. Specifically, starting from the material synthesis end, the charging and discharging performance (charging and discharging capacity) is improved through two optimizations. The first point is mainly to synthesize small-particle lithium iron phosphate materials through macroscopic control under the premise of ensuring the compaction density, shorten the diffusion path of lithium ions, and improve the charging and discharging capacity of the battery core; the second point is mainly to modify the lithium iron phosphate material through microscopic doping, introduce heterogeneous metal elements in the material synthesis process, realize heterogeneous metal element doping, and form a skeleton charging channel to improve the conductivity of the material, thereby improving the charging and discharging performance of the material.

[0020] The present invention mainly improves the charging performance of lithium iron phosphate by reducing the particle size of lithium iron phosphate particles and selectively controlling the doping amount of Ti element, which is more specifically as follows:

[0021] 1. Reduce the particle size of lithium iron phosphate particles, control D50 at 0.7-0.9μm, improve the dynamic performance of lithium iron phosphate materials, ensure the stability of the physical properties of the materials, and reduce the impact of the decrease in specific capacity caused by the side reactions caused by the reduction in particle size and the decrease in energy density caused by the decrease in compaction density;

[0022] 2. Adding Ti element during the sintering process of lithium iron phosphate, Ti element is doped in lithium iron phosphate material to form a titanium skeleton, which provides more lithium ion deintercalation channels during the charging process and improves the electronic conductivity of the material to a certain extent. The enhanced conductivity further improves its electrochemical performance, thereby reducing the polarization of the charging process, so that charging does not need to be terminated early, the actual charging time is extended, the constant power charging capacity is increased, and finally the discharge capacity of the battery is increased. From the perspective of material structure, Ti 4+ The ionic radius of Li + The same, more inclined to occupy the Li position, reducing the interplanar spacing and particle size, will form Fe in the lattice 2+ and Fe 3+ The mixed valence state of Ti 4+ The modification effect is not significant if the content is too low. 4+Too high will block Li + The deintercalation channel of the charging process, therefore, the addition of 2000-6000ppm of Ti has a significant improvement on the electrochemical properties of the material. Titanium dioxide with high cost performance is preferred as the titanium source, and the particle size of titanium dioxide is controlled between 200-300nm, which increases the number of lithium ion deintercalation channels and reduces charging polarization.

[0023] The present invention finally solves the problem of low discharge capacity of lithium iron phosphate positive electrode material by improving charging performance, especially charging capacity. The energy density of the lithium iron phosphate battery of the present invention is not less than 172Wh / kg, and the compaction density of the lithium iron phosphate material is not less than 2.45g / cm 3 , the gram capacity is not less than 143mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 This is a flow chart of the preparation and testing of lithium iron phosphate materials of the present invention;

[0026] Figure 2 This is a comparison diagram of constant current and constant voltage charging and discharging and constant power charging and discharging curves of lithium iron phosphate material in Example 3 of the present invention;

[0027] Figure 3 for Figure 2 A partial enlarged view of the tail of constant current and constant voltage charging and constant power charging;

[0028] Figure 2 , 3 In the figure, the four lines from top to bottom are: upper solid line - constant power charging curve, upper dotted line - constant current and constant voltage charging curve; lower dotted line - constant current discharge curve, lower solid line - constant power discharge curve. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0030] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0031] In the present invention, the terms used have the common meanings in the art, mainly including the following:

[0032] Specific capacity refers to the capacity that a battery or active material can output / release per unit mass or volume, i.e., mass specific capacity and volume specific capacity. Unless otherwise specified in the present invention, it refers to mass specific capacity, usually in units of ampere-hour per kilogram (Ah / kg) and milliampere-hour per gram (mAh / g). Specific capacity usually indicates the discharge capacity of a battery.

[0033] Gram capacity refers to the ratio of the capacity that can be released by the active material inside the battery to the mass of the active material. It is usually expressed in milliampere hours per gram (mAh / g), reflecting the amount of electricity that can be provided by each gram of active material.

[0034] Battery capacity refers to the amount of electricity that can be obtained from a battery under certain discharge conditions. The unit is generally A·h or mA·h, and it is divided into theoretical capacity, rated capacity and actual capacity. Theoretical capacity refers to the amount of electricity calculated according to Faraday's law of electrolysis when all the active substances in the positive and negative electrodes of the battery participate in the redox reaction to form current. The rated capacity is the minimum capacity that the battery should discharge under certain discharge conditions when designing and manufacturing the battery. Actual capacity refers to the amount of electricity actually obtained from the battery under certain discharge conditions. The actual capacity of a battery is always lower than the theoretical capacity.

[0035] Charge capacity refers to the amount of charge a battery can accept.

[0036] Discharge capacity refers to the amount of charge that a battery can release.

[0037] Energy density refers to the energy stored in a battery per unit volume or per unit mass, usually in units of Wh / L or Wh / kg. Energy density usually indicates the storage capacity of a battery per unit volume or per unit mass.

[0038] According to a first aspect of the present invention, a lithium iron phosphate material is provided, wherein the lithium iron phosphate material is spherical lithium iron phosphate particles doped with Ti element, the doping amount of the Ti element is 2000-6000 ppm, and the D50 of the spherical lithium iron phosphate particles is 0.7-0.9 μm.

[0039] The inventor has found through research that during the constant power charging process of lithium iron phosphate positive electrode materials, as the battery SOC level increases, the charging polarization gradually increases, resulting in the battery being unable to be fully charged during constant power charging, which in turn leads to a low discharge capacity, thereby affecting the capacity of the lithium iron phosphate material. In order to solve the problem that the polarization at the end of constant power charging is large, the battery cannot be fully charged, resulting in a low discharge capacity, the solution is to reduce the polarization of the lithium iron phosphate material during constant power charging and improve the capacity. The solution is to start with the material synthesis end to improve it. By optimizing the synthesis of lithium iron phosphate materials, the particle size of lithium iron phosphate materials is reduced, and its kinetic performance is improved. At the same time, the polarization degree at the end of charging is reduced, and the constant power charging capacity is increased, and the capacity is finally improved. However, after the particle size of lithium iron phosphate particles is reduced, there are two negative effects. First, the electrochemical performance of lithium iron phosphate materials is affected, mainly because the electrochemical stability will decrease, because the reduction in particle size leads to an increase in specific surface area, which in turn increases the side reaction and leads to a decrease in specific capacity; second, it affects the processing performance, mainly affecting the compaction density of the material, resulting in a decrease in the energy density of the battery, and ultimately lowering the cost performance of the product.

[0040] Therefore, the synthesis of the lithium iron phosphate material of the present invention is finally optimized around two points: the first point is to control the particle size of the lithium iron phosphate material, synthesize the lithium iron phosphate material with a smaller particle size while ensuring the compaction density, and shorten the Li + The diffusion path in the lithium iron phosphate material increases the lithium ion diffusion coefficient, improves its kinetic performance (macroscopically manifested as low impedance and good conductivity), increases the charge capacity per unit time, and avoids simply reducing the particle size, which only increases the conductivity of the material and increases the charge capacity but sacrifices the processing performance (i.e., compaction) of the material; the D50 of the lithium iron phosphate material of the present invention can be typically but not limitedly selected to be 0.71 μm, 0.73 μm, 0.75 μm, 0.77 μm, 0.79 μm, 0.81 μm, 0.83 μm, 0.85 μm, 0.87 μm, 0.89 μm, etc.;

[0041] The second point is to dope and modify the material. In the solid phase synthesis of lithium iron phosphate material, an appropriate amount of Ti element is selected to dope so that it forms a titanium skeleton in the lithium iron phosphate material, providing more lithium ion deintercalation channels during the charging process, and improving the electronic conductivity of the material to a certain extent. The enhanced conductivity further improves the electrochemical properties of the material, thereby reducing the polarization of the charging process, so that the charging does not need to be terminated in advance, the actual charging time is extended, the constant power charging capacity is improved, and the discharge capacity of the battery is finally improved. The doping amount of the Ti element in the lithium iron phosphate material of the present invention is typically but not limitedly selected to be 2050ppm, 2200ppm, 2400ppm, 2600ppm, 2800ppm, 3000ppm, 3200ppm, 3400ppm, 3600ppm, 3800ppm, 4000ppm, 4200ppm, 4400ppm, 4600ppm, 4800ppm, 5000ppm, 5200ppm, 5400ppm, 5600ppm, 5800ppm, 5950ppm, etc.

[0042] Therefore, the compacted density of the lithium iron phosphate material synthesized by the present invention is not less than 2.45g / cm 3 The gram capacity is not less than 143mAh / g, and after being applied to lithium-ion batteries, it can reduce charging polarization, and the energy density of the battery is not less than 172Wh / kg. In fact, it not only guarantees the charging capacity of the material but also ensures the compaction density of the material, ultimately improving the energy density of the battery and improving the cost performance of the battery.

[0043] According to the second aspect of the present invention, a lithium iron phosphate material is also a method for preparing the lithium iron phosphate material described in the first aspect. First, a lithium source, an iron source, a phosphorus source and a titanium source are dispersed by ball milling to make the powders evenly mixed, and then high-temperature calcination, natural cooling and then crushing by air flow milling to obtain a lithium iron phosphate material with spherical particles with a D50 of 0.7 to 0.9 μm, wherein the doping amount of the Ti element in the lithium iron phosphate material is 2000 to 6000 ppm.

[0044] In the preparation method of the present invention, the lithium iron phosphate material is mainly modified and synthesized by a solid phase sintering method. The solid phase sintering method is a conventional synthesis method of lithium iron phosphate, and the preparation cost is relatively low, which is conducive to improving the cost performance of the battery.

[0045] As an optional embodiment of the preparation method of the present invention, the titanium source is selected from one or more of oxides, hydroxides, chlorides, and fluorides containing titanium. Preferably, the titanium source is selected from titanium dioxide, which has the highest cost performance. More preferably, the D50 of the titanium dioxide is 200-300nm (such as 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, etc.).

[0046] In the present invention, the lithium source, iron source and phosphorus source in the raw materials for synthesis of lithium iron phosphate are not particularly limited, and any conventional raw materials available in the art can be used. For example, the lithium source is selected from one or more of lithium hydroxide monohydrate, lithium acetate, lithium nitrate, lithium fluoride, lithium carbonate, lithium oxalate and lithium hydroxide; the iron source is selected from one or more of ferrous oxide, ferrous oxide, iron powder, ferric phosphate, ferrous oxalate, ferric acetate and ferric nitrate; the phosphorus source is selected from one or more of diammonium phosphate, monoammonium hydrogen phosphate, ferric phosphate and lithium dihydrogen phosphate.

[0047] As an optional embodiment of the preparation method of the present invention, the temperature of the high temperature calcination is 650°C-850°C (such as 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, etc.).

[0048] As an optional implementation of the preparation method of the present invention, the high-temperature calcination time is 8 to 10 hours (such as 8.5 hours, 9 hours, 9.5 hours, etc.).

[0049] According to a third aspect of the present invention, an application of the lithium iron phosphate material described in the first aspect or the lithium iron phosphate material prepared by the preparation method described in the second aspect.

[0050] The lithium iron phosphate material of the present invention can be widely used because of its balanced specific capacity and compaction density. However, it is particularly prominent in its application as a positive electrode material in lithium-ion batteries, which can reduce charging polarization, so that the lithium-ion batteries have higher energy density and discharge capacity.

[0051] As an optional implementation of the application of the lithium iron phosphate material of the present invention, the negative electrode active material of the lithium ion battery is graphite.

[0052] As an optional implementation of the application of the lithium iron phosphate material of the present invention, the energy density of the lithium ion battery is not less than 172Wh / kg.

[0053] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0054] Examples 1-6 and Comparative Examples 1-3

[0055] According to the attached Figure 1 The process shown is to prepare lithium iron phosphate materials, prepare batteries, and test capacity and energy. The details are as follows:

[0056] (1) Preparation of lithium iron phosphate

[0057] First, the lithium source, iron source, phosphorus source and titanium source are dispersed by ball milling to make the powders evenly mixed, and then high-temperature calcination is carried out at a temperature of 650°C-850°C, and the calcination time is controlled at 8-10 hours to form a primary product. After then naturally cooled to room temperature, a gas flow milling method is used to obtain a lithium iron phosphate positive electrode material with spherical particles with a particle size D50 of 0.5-0.9 microns.

[0058] Among them, the lithium source is selected from lithium carbonate, the iron source is selected from ferrous oxide, the phosphorus source is selected from iron phosphate, and the titanium source is selected from titanium dioxide with a D50 of 200-300nm. The present invention synthesizes three groups of lithium iron phosphate materials with different particle size distributions and three groups of titanium contents with exactly the same preparation process, and obtains nine lithium iron phosphate materials with different physical properties, which are Examples 1-6 and Comparative Examples 1-3, as shown in Table 1.

[0059] (2) Preparation of batteries

[0060] The modified lithium iron phosphate material prepared in (1) was used as a positive electrode active material, and was mixed with a conductive agent SP and a binder PVDF in a mass ratio of 95:2:3 to form a slurry, which was then coated on an aluminum foil to obtain a positive electrode sheet with a thickness of 210 μm. Graphite was used as a negative electrode active material, and was mixed with a conductive agent SP, a binder CMC, and a thickener SBR in a mass ratio of 94:1.5:2.5:2 to form a slurry, which was then coated on a copper foil to obtain a negative electrode sheet with a thickness of 120 μm. The positive electrode sheet, the negative electrode sheet, and a PE separator were stacked and assembled into a battery cell, which was placed in an aluminum-plastic film shell, and then subjected to top and side sealing, baking, liquid injection, formation, and volume separation to obtain a finished battery cell. The electrolyte injected was 1.0 mol / L LiPF 6 The solvent is ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 3:3:4.

[0061] (3) Constant current, constant voltage, and constant power charging and discharging tests

[0062] Nine groups of lithium iron phosphate materials with different physical properties were analyzed as controls, charged to 3.75V at 0.5C, and then discharged to 2.5V at 0.5C, the capacity of the battery was recorded, and batteries with a capacity difference of less than 0.5% were selected for charging verification to avoid test errors caused by battery differences. The selected batteries with good consistency were randomly divided into two groups, one of which was charged with 0.5C constant current and constant voltage and discharged with 0.5C constant current, that is, constant current and constant voltage charging and discharging tests were performed. Since the end of constant current and constant voltage charging was a constant voltage charging process (3.75V), the charging current in this process gradually decreased, so that the battery polarization gradually decreased, and the battery could be close to a full state; the other group was charged and discharged with 0.5P constant power, and the cut-off voltage was 3.75V, that is, constant power charging and discharging tests were performed. The voltage was used as the charging cut-off condition at the end of constant power charging, and there was no passivation process; the ratio of 0.5P constant power discharge capacity to 0.5C constant current discharge capacity was calculated to determine the actual reduction of polarization of the lithium iron phosphate materials obtained in the embodiments and comparative examples as positive electrode materials in lithium battery applications, and the specific data results are shown in Table 1.

[0063] Table 1 Material properties of different groups and comparison of constant current, constant voltage and constant power charging and discharging

[0064]

[0065] pass Figure 2 , 3 It can be seen that for the same battery, the final charging capacity is different when using constant current and constant voltage charging and constant power charging, and the discharge capacity is also different. However, further looking at the specific data results of constant current and constant voltage charging and discharging coulombic efficiency, constant power coulombic efficiency and constant power discharge capacity / constant current discharge capacity ratio in Table 1, the coulombic efficiency of the two charging and discharging methods is above 99.9%, and the capacity loss during the discharge process is extremely small, indicating that the polarization of the discharge process of the two charging and discharging methods can be ignored; the size of the capacity ratio mainly depends on the capacity charged during the charging process. The higher the charging capacity, the higher the discharge capacity, the higher the ratio, and the lower the polarization. It can be seen that when the lithium iron phosphate material of the present invention is used as a positive electrode material in a lithium-ion battery, it can effectively reduce the polarization phenomenon at the end of constant power charging, so that the battery is close to a full state, avoiding the problem of low discharge capacity caused by the inability to be fully charged.

[0066] Further test results show that when constant power charging and discharging is adopted, the discharge capacity increases gradually with the decrease of lithium iron phosphate particle size in different Ti content groups, and the energy density of the corresponding battery cell of titanium content group 2 shows a trend of increasing first and then decreasing. This is because on the one hand, the particle size is positively correlated with the diffusion path of lithium ions in lithium iron phosphate, that is, the diffusion distance of lithium ions can be effectively shortened by reducing the particle size, but with the decrease of lithium iron phosphate material particle size, first, the compaction density of the material will be further reduced, and second, the side reactions brought about by the increase of material specific surface area during the charging and discharging process will also increase, which will have a negative impact on the battery capacity. Therefore, through appropriate material particle size control, the particle size of lithium iron phosphate material is controlled within 0.7-0.9μm, which not only ensures the improvement of material kinetic performance, but also ensures the stability of physical properties, reduces the influence of the decrease of specific capacity caused by side reactions and the decrease of energy density caused by compaction density, and can effectively improve the comprehensive performance of the battery, and obtain the balanced specific capacity, compaction density and energy density.

[0067] By comparing the experimental results of different titanium content groups under the same particle size distribution, it can be found that in terms of energy density, titanium content group 2> titanium content group 3> titanium content group 1; and when the titanium content is 4000ppm and the particle size is 0.7μm, the comprehensive performance of the lithium iron phosphate material is the best, specifically, the energy density of the battery cell is as high as 175.2Wh / kg. This is because the titanium element is doped in the lithium iron phosphate material to form a titanium skeleton, which provides more lithium ion deintercalation channels during the charging process and improves the electronic conductivity of the material to a certain extent. The enhanced conductivity further improves its electrochemical performance, thereby reducing the polarization of the charging process, so that charging does not need to be ended early, the actual charging time is extended, the constant power charging capacity is increased, and ultimately the discharge capacity of the battery is increased. From the perspective of material structure, due to the Ti 4+ The ionic radius of Li + The same, more inclined to occupy the Li position, reducing the interplanar spacing and particle size, will form Fe in the lattice 2+ and Fe 3+ The mixed valence state of Ti 4+ If the content is too low, the modification effect of gram capacity is not significant. 4+ Too high will block Li + In the deintercalation channel of the charging process, the appropriate amount of Ti doping has a significant improvement on the electrochemical properties of the material. Therefore, by properly regulating the Ti doping amount, the Ti doping amount of the lithium iron phosphate material is controlled within 2000-6000ppm, reducing polarization while obtaining a balanced specific capacity, compaction density and energy density.

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the claims of the present invention.

Claims

1. A lithium iron phosphate material, characterized in that: The lithium iron phosphate material is quasi-spherical lithium iron phosphate particles doped with Ti element, the doping amount of the Ti element is 2000-6000 ppm, and the D50 of the quasi-spherical lithium iron phosphate particles is 0.7-0.9 μm.

2. The lithium iron phosphate material according to claim 1, characterized in that: The compaction density of the lithium iron phosphate material is not less than 2.45 g / cm 3 , the gram capacity is not less than 143mAh / g.

3. A method for preparing a lithium iron phosphate material, characterized in that: First, the lithium source, iron source, phosphorus source and titanium source are dispersed by ball milling to make the powders uniformly mixed, and then calcined at high temperature, naturally cooled and crushed by air flow milling to obtain a lithium iron phosphate material with spherical particles with a D50 of 0.7 to 0.9 μm, wherein the doping amount of the Ti element in the lithium iron phosphate material is 2000 to 6000 ppm.

4. The preparation method according to claim 3, characterized in that: The titanium source is titanium dioxide.

5. The preparation method according to claim 4, characterized in that: The D50 of the titanium dioxide is 200-300 nm.

6. The preparation method according to claim 3, characterized in that: The high temperature calcination temperature is 650°C-850°C.

7. The preparation method according to claim 3, characterized in that: The high temperature calcination time is 8 to 10 hours.

8. An application of lithium iron phosphate material, characterized in that: The application includes using the lithium iron phosphate material described in any one of claims 1-2 or the lithium iron phosphate material prepared by the preparation method described in any one of claims 3-7 as a positive electrode material of a lithium ion battery, so as to reduce charging polarization.

9. The use according to claim 8, characterized in that The negative electrode active material of the lithium ion battery is graphite.

10. The use according to claim 8, characterized in that The energy density of the lithium-ion battery is not less than 172Wh / kg.

Citation Information

Patent Citations

  • Lithium iron phosphate positive electrode material as well as preparation method and application thereof

    CN113800493A

  • High-tap-density lithium iron phosphate positive electrode material as well as preparation method and application thereof

    CN114804058A

  • Lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery

    CN115072694A

  • Mixed material for improving low-temperature performance of high-compaction lithium iron phosphate as well as preparation method and application of mixed material

    CN116454271A

  • Doped lithium iron phosphate and preparation method thereof, positive electrode material, positive plate and lithium battery

    CN116960321A